Real-World HbA1c Changes Among Type 2 Diabetes Mellitus Patients Initiating Treatment With a 1.0 Mg Weekly Dose of Semaglutide for Diabetes - Noelle N. Gronroos; Caroline Swift; Monica S. Frazer; Andrew Sargent; Michael Leszko; Erin Buysman; Sara Alvarez; Tyler J. Dunn; Josh Noone (Journal of Health Economics and Outcomes Research)
**Background:** Medical management of patients with type 2 diabetes mellitus (T2DM) is complex because of the chronic nature of the disease and its associated comorbidities. Injectable once-weekly semaglutide for diabetes (OW sema T2D) is a type of glucagon-like peptide–1 receptor agonist approved for the treatment of patients with T2DM. **Objectives:** To describe patient characteristics and HbA1c changes for patients prescribed 1.0 mg maintenance dose OW sema T2D. **Methods:** This retrospective study included adult patients with T2DM with a pre-index glycated hemoglobin (HbA1c) of at least 7%, initiating treatment with OW sema T2D between January 1, 2018, and December 31, 2019, and prescribed a 1.0 mg maintenance dose. Patients were identified in the Optum Research Database and were included if they had continuous health plan enrollment for at least 12 months prior to (pre-index) and at least 12 months following (post-index) the date of the first OW sema T2D claim (index). Dose at initiation and prescriber specialty were captured. Change in HbA1c between the latest post-index and pre-index HbA1c measurement was calculated among all patients and among those with at least 90 days of continuous treatment (persistent patients). **Results:** A total of 2168 patients were included in this study. On average, patients were taking 13.5 different classes of medications. The majority of patients had lipid metabolism disorder (90.8%), hypertension (86.6%), diabetes with complications (86.8%), or other nutritional/endocrine/metabolic disorders (72.5%). The mean HbA1c reduction was 1.2% (P < .001). Patients persistent with OW sema T2D (n =1280) had a mean HbA1c reduction of 1.4% (P < .001). The mean (SD) days covered with a 1.0 mg maintenance dose was 236.1 (94.1) days. **Discussion:** Despite being medically complex, the patients in this real-world study experienced significant reductions in HbA1c following initiation of OW sema T2D. **Conclusions:** A 1.0 mg maintenance dose of OW sema T2D is an effective treatment for T2DM in the real world.